The region-of-origin (ROO) effect on purchasing preferences. Issue 2 (2nd February 2015) - Chamorro, Antonio; Rubio, Sergio; Miranda, F. Javier
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyse the "region-of-origin" effect in the purchase of cava, a sparkling wine. Cava is a multiregional designation of origin: although it is a product typical of a particular Spanish region (Catalonia), it is also produced in other regions in Spain. Design/methodology/approach – The technique of conjoint analysis is used to identify the structure of the preferences of cava consumers, and to evaluate how that structure is affected by the inclusion of a message that highlights the regional origin of the product. A survey was conducted among 473 wine buyers in the region of Extremadura (Spain). Findings – The main findings show that the "region-of-origin" effect is significant for the regional buyer of this type of wine, and that the sales of regional brands of cava would be greater if their regional origin were emphasized by indicating the location of the producer in a prominent place on the label. Moreover, three segments of purchasers differentiated by their preference structure are identified. Originality/value – The novelty of the study lies in the fact that this PDO is a multiregional designation of origin, and that the technique used, conjoint analysis, is applied not only to determine the buyer's preference structure, but also to evaluate how that structure is affected when the regional origin of the product is highlighted in the message to the purchaser. This study is of value to academic researchers, wineries managers, and regional governments as it highlights important aspects to design marketing strategies and trade policies.